Carraher's polymer chemistry - Carraher, Charles E.; Seymour, Raymond B. (Raymond Benedict), 1912-1991. (Boca Raton, FL : CRC Press, 2011)
'Updated to reflect a growing focus on green chemistry in the scientific community and in compliance with the American Chemical Society's Committee on professional training guidelines, Carraher's polymer chemistry, eighth edition integrates the core areas that contribute to the growth of polymer science. It supplies the basic understanding of polymers essential to the training of science, biomedical, and engineering students. New in the eighth edition: updating of analytical, physical, and special characterization techniques. Increased emphasis on carbon nanotubes, tapes and glues, butyl rubber, polystyrene, polypropylene, polyethylene, poly(ethylene glycols), shear-thickening fluids, photo-chemistry and photophysics, dental materials, and aramids. New sections on copolymers, including fluoroelastomers, nitrile rubbers, acrylonitrile-butadiene-styrene terpolymers, and EPDM rubber. New units on spliceosomes, asphalt, and fly ash and aluminosilicates. Larger focus on the molecular behavior of materials, including nano-scale behavior, nanotechnology, and nanomaterials. Continuing the tradition of providing a user-friendly approach to the world of polymeric materials, the book allows students to integrate their chemical knowledge and establish a connection between fundamental and applied chemical information. It contains all of the elements of an introductory text with synthesis, property, application, and characterization. Special sections in each chapter contain definitions, learning objectives, questions, and additional reading, and case studies are woven into the text fabric. Symbols, trade names, websites, and other useful ancillaries appear in appendices to supplement the text'--
'This new edition of Carraher's Polymer Chemistry maintains the scope and organization of its bestselling predecessors, while fulfilling the ACS-CPT advanced course requirement. Emphasizing the fundamental behavior of polymers in nature reflected in technological developments, it features new chapters on composites, fibers, and naturally occurring polymers in plants and animals. It also highlights nanoscale polymer applications with new sections on drug design, electronics, optical fibers, textiles, and adhesives. Each chapter includes study tips, glossaries, and exercises. This edition also expands listings for lab exercises, polymer structures, trade names, and Internet resources. Professors adopting the text will be aided by a test-bank available for their exclusive use'--
Rev ed. of : Seymour/Carraher's polymer chemistry / Raymond B.Seymour, 6th ed., 2003
Includes bibliographical references and index.
Keywords: Polymers; Polymerization